Wenzi Jiedu Recipe ameliorates colorectal cancer by remodeling the gut microbiota and tumor microenvironment - Qiu, Wenli; Sang, Tianqing; Chen, Haibin; Zhou, Hongli; Wang, Zhongqiu; Zhou, Hongguang (Frontiers in Oncology, 2022)
Introduction Wenzi Jiedu Recipe (WJR), traditional Chinese medicine (TCM) formula, has been proven to be clinically useful in the treatment of colorectal cancer (CRC). However, its underlying mechanisms are still elusive, which limits its wider application. Thus, we aimed to evaluate the effect of WJR on CRC and elucidate mechanisms underlying its action. Methods Network pharmacology was employed to clarify the “herb-active ingredient-target” network of WJR. The 16S rDNA sequencing method was used to analyze the changes of gut microbes mediated by WJR in tumor-bearing mice with CRC. The proportions of CD4+ T cell and CD8+ T cell were measured by flow cytometry. Levels of the cytokines interleukin (IL)-10, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α were assessed by immunohistochemistry and enzyme-linked immunosorbent assay (ELISA). Results WJR showed significant anti-CRC effects both in vitro and in vivo. Network pharmacology revealed that WJR exerts anti-CRC therapeutic effect on multiple targets and signaling pathways. Gut microbiota analysis revealed that WJR therapy significantly enriched for Oscillibacter and Bacteroides_acidifacien. In particular, we found that WJR significantly increased the proportion of CD8+ T cells and the expression of immune-associated cytokines IL-10, IFN-γ, and TNF-α. Conclusion The regulation of gut microbiota by WJR may be the breakthrough point to clarify its mechanism of action in the treatment of CRC, and it has a good prospect of clinical application.